Environmental flows in the context of unconventional natural gas development in the Marcellus Shale. Issue 1 (4th January 2017) - Buchanan, Brian P.; Auerbach, Daniel A.; McManamay, Ryan A.; Taylor, Jason M.; Flecker, Alexander S.; Archibald, Josephine A.; Fuka, Daniel R.; Walter, M. Todd
Abstract: Quantitative flow–ecology relationships are needed to evaluate how water withdrawals for unconventional natural gas development may impact aquatic ecosystems. Addressing this need, we studied current patterns of hydrologic alteration in the Marcellus Shale region and related the estimated flow alteration to fish community measures. We then used these empirical flow–ecology relationships to evaluate alternative surface water withdrawals and environmental flow rules. Reduced high‐flow magnitude, dampened rates of change, and increased low‐flow magnitudes were apparent regionally, but changes in many of the flow metrics likely to be sensitive to withdrawals also showed substantial regional variation. Fish community measures were significantly related to flow alteration, including declines in species richness with diminished annual runoff, winter low‐flow, and summer median‐flow. In addition, the relative abundance of intolerant taxa decreased with reduced winter high‐flow and increased flow constancy, while fluvial specialist species decreased with reduced winter and annual flows. Stream size strongly mediated both the impact of withdrawal scenarios and the protection afforded by environmental flow standards. Under the most intense withdrawal scenario, 75% of reference headwaters and creeks (drainage areas <99 km 2 ) experienced at least 78% reduction in summer flow, whereas little change was predicted for larger rivers. Moreover, the least intense withdrawal scenario still reduced summer flows by at least 21% for 50% of headwaters and creeks. The observed 90th quantile flow–ecology relationships indicate that such alteration could reduce species richness by 23% or more. Seasonally varying environmental flow standards and high fixed minimum flows protected the most streams from hydrologic alteration, but common minimum flow standards left numerous locations vulnerable to substantial flow alteration. This study clarifies how additional water demands in the region may adversely affect freshwater biological integrity. The results make clear that policies to limit or prevent water withdrawals from smaller streams can reduce the risk of ecosystem impairment.